Theoretical Design of Asymmetric/symmetric Nanodisk Arrays Deposited on GaAs Film for Plasmonic Modulation and Sensing - Cheng SUN; Xue YANG; Xinyu LI; Shuwen CHU (Medžiagotyra)
Metallic plasmonic nanostructures can achieve nanoscale light-matter interactions and have a wide range of applications in spectral modulation and optical sensing fields stemming from their rich and tunable optical properties. Herein, we propose a composite nanostructure consisting of a gold nanodisk array and a GaAs thin film, which achieves symmetric and asymmetric configurations by adjusting the nanodisk radius of the array structure. We systematically investigate the relationship between plasmonic modulation and asymmetric/symmetric coupling modes. The results indicate that the two configurations correspond to single resonance and dual resonance, respectively. The short wavelength of the dual-resonant mode is jointly excited by the local surface plasmon polariton (LSP) mode of the nanodisk itself and the waveguide-hybridized lattice mode of the bottom GaAs film. And the long wavelength corresponds to the LSP mode of the array nanostructure which strongly depends on its size.  Improving structural symmetry leads to different trends in resonance wavelength. Furthermore, we investigate the sensing performances for asymmetric/symmetric nanodisk arrays. This work is of great significance for applications such as multi-resonance sensing, plasmonic modulation, etc.